Music and Spirituality: An Auto-Ethnographic Study of How Five Individuals Used Music to Enrich Their Soul - Bist, Dinesh; Shuttleworth, Mark 19XX-; Smith, Laura; Smith, Peter; Walker-Gleaves, Caroline (2024)
This paper presents a study of the experiences of five individuals who explore their unique relationship between music and spirituality. Each participant critically narrates their faith and beliefs and explores how these relate to their experiences with music. The paper begins with a brief exposition of the literature concerning music and spirituality and the linkages between the two. The methodology combines narrative and auto-ethnography, underpinned by a phenomenological approach to reflection on experiences. Using deep self-analysis, the five authors derive and discover lessons concerning their own relationship between faith, spirituality, and music. These are then analysed to produce common themes concerning the intertwining of spirituality with music. Finally, the conclusions present a novel contribution which includes lessons on how through self-exploration, one can use music and spirituality to repair and ultimately enrich the soul. The paper exposes the interplay between faith, spirituality and music, which will be of general interest and provide inspiration to those who intend to use music to enrich their lives and heal themselves.
Keywords: Growth; Healing; Religion; Experiences; thematic; Phenomenology; Auto-ethnography; Narrative; Spirituality; Music